2016
DOI: 10.4253/wjge.v8.i9.391
|View full text |Cite
|
Sign up to set email alerts
|

First report of splenic rupture following deep enteroscopy

Abstract: Splenic rupture is a rare complication of diagnostic and therapeutic gastrointestinal endoscopy procedures. Herein, we report for the first time a case of splenic rupture following therapeutic retrograde double-balloon enteroscopy, which occurred in an 85-year-old man who was treated for recurrent mid-intestinal bleeding that resulted from ileal angioectasia. This patient promptly underwent an operation and eventually recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[ 10 ] However, no such complication occurred in this study, suggesting that during enteroscopy through the mouth, the operator reduced the gas flow in the intestine to reduce the pressure in the intestinal tract. Splenic rupture following deep enteroscopy has also been reported,[ 11 ] but did not occur in this study; our experience showed that brute force should be avoided when the scope is being moved forward and backward.…”
Section: Discussionmentioning
confidence: 47%
“…[ 10 ] However, no such complication occurred in this study, suggesting that during enteroscopy through the mouth, the operator reduced the gas flow in the intestine to reduce the pressure in the intestinal tract. Splenic rupture following deep enteroscopy has also been reported,[ 11 ] but did not occur in this study; our experience showed that brute force should be avoided when the scope is being moved forward and backward.…”
Section: Discussionmentioning
confidence: 47%
“…138 publications (7 case series and 131 singular case reports) were included of 163 individual patients treated primarily with splenectomy for splenic laceration after colonoscopy 11,14,15,17–19,31,33,34,40,42,45,50,52–176 . Individual patient data are shown in Supplementary Table and presented in comparison to SAE and splenorrhaphy in Table 1.…”
Section: Resultsmentioning
confidence: 99%